Hurtig og sikker tilgang til informationer om ordforbindelser - Bergenholtz, Henning (LexicoNordica, 2009)
Only 10 or 15 years ago, you had to spend hours, days or even weeks in libraries to find data of many kinds. Today, we have access to many data at our home desks. Therefore, the biggest problem for a real information society is not that you do not have access to the needed data, but that you cannot find them or that it takes so long to find them that you give up the search before finding the result. This is clearly shown by a Google search where you get so many results that we have a case of information stress or even worse information death. An easy and secure search route and a short search time are important elements when certain information needs are to be fulfilled. This topic is discussed based on an experiment concerning certain fixed expressions in seven Danish printed and electronic dictionaries.